Effects of Different Weather Conditions and Addition of Mangosteen Peel Powder on Chemical Properties and Antioxidant Activity of Coconut Sap - Pepita Haryanti; Supriyadi Supriyadi; Djagal Wiseso Marseno; Umar Santoso (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Coconut sap is sweet, oyster-white and translucent liquid which can be obtained by tapping coconut flowers for 8 ̶ 12 hours. Since it contains sugar with nearly neutral pH, coconut sap is highly susceptible to spontaneous fermentation. In order to maintain the quality of the sap during the tapping process, coconut farmers usually add preservative substances. The preservatives can be produced either naturally, such as mixtures of lime, mangosteen peel and sliced jackfruit wood, or synthetic one, such as sodium metabisulphite. The chemical properties of coconut sap might be affected by weather conditions during the tapping process. This research aimed to determine the effect of weather conditions during tapping process and variations of mangosteen peel powder concentration on the chemical properties and antioxidant activity of the coconut sap. The results showed that the optimum preservative concentration of mangosteen peel powder was 0.84 g/L of coconut sap which was tapped in sunny weather condition. This treatment yielded sap with chemical properties i.e. pH value of 6.7; total soluble solids of 16.2 °brix; water content of 85.62%; reducing sugar of 0.04 g/100 g; sucrose content of 13.64 g/100 g; total free amino acids of 0.1738 g/100 g; total phenolic of 323.23 mgGAE/100 g; and vitamin C of 26.06 mg/100 g. The antioxidant activity of this treatment was 34.39 % RSA evaluated by DPPH method, this value, was relatively similar to that of the addition of 0.28 and 0.56 g/L mangosteen peel powder. The coconut sugar produced had reducing sugar of 5.01 g/100 g; total sugar of 86.50 g/100 g; total phenolic content of 470 mgGAE/100 g; browning index of 16254 IU (ICUMSA); and antioxidant activity of 61.05% RSA.